Deconstructing the multi-layered nature of citizen participation in Vietnam: conceptual connotations, discourses of international development, and the country's institutional context. Issue 3 (2nd September 2019) - Kwak, Seohee
ABSTRACT: Citizen participation is challenging to define in terms of meaning and application. This article begins with setting out the multi-dimensional nature of citizen participation in development. Through conceptual and contextual explorations, this article deconstructs the layers in the following ways: First, citizen participation is embedded with several conceptual connotations, therefore it is manifested to varying degrees and in different scopes of opportunity for citizens to affect policy decisions. Varieties of participation become more diverse when it comes to the power dynamics of different stakeholders, ranging from the government to citizens. Furthermore, its substantive presentation is intimately linked with the variables of citizen empowerment and government responsiveness. The second layer concerns the participatory development approaches of external development agencies. This article articulates how development discourses have integrated and developed the concept of participation, exploring the trajectory and critical concerns raised. The final layer concerns context, particularly Vietnam's legal and policy frameworks, which explores consistencies and discrepancies between institutional settings and the presentation of citizen participation.